Is It Biased? Empirical Analysis of Various Phenomena That Affect Survey Results : Postoji li pristranost? Empirijska analiza različitih fenomena koji utječu na rezultate anketnih istraživanja - Mandić, Luka (Array, 2021)
It is often assumed that survey results reflect only the quality of the sample and the underlying measuring instruments used in the survey. However, various phenomena can affect the results, but these influences are often neglected when conducting surveys. This study aimed to test the influences of various method effects on survey results. We tested the influences of the following method effects: item wording, confirmatory bias, careless responding, and acquiescence bias. Using a split-ballot survey design with online questionnaires, we collected data from 791 participants. We tested if these method effects had an influence on mean values, item correlations, construct correlations, model fits, and construct measurement invariance. The instruments used to test these influences were from the domain of personality and gender inequality, and their items were adapted based on the method effect tested. All tested method effects, except careless responding, had a statistically significant effect on at least one component of the analysis. Item wording and confirmatory bias affected mean values, model fit, and measurement invariance. Controlling for acquiescence bias improved the fit of the model. This paper confirms that the tested method effects should be carefully considered when using surveys in research, and suggests some guidelines on how to do so.